Calibration of an Upconverting Phosphor-Based Quantitative Immunochromatographic Assay for Detecting Yersinia pestis, Brucella spp., and Bacillus anthracis Spores - Zhang, Pingping; Zhang, Yuanyuan; Zhao, Yong; Song, Yajun; Niu, Chunyan; Sui, Zhiwei; Wang, Jing; Yang, Ruifu; Wei, Dong (Frontiers in Cellular and Infection Microbiology, 2020)
Yersinia pestis, Brucella spp., and Bacillus anthracis are pathogens that can cause infectious zoonotic diseases with high mortality rates. An upconverting phosphor-based quantitative immunochromatographic (UPT-LF) assay, a point-of-care testing method suitable for resource-limited areas, was calibrated to quantitatively detect pathogenic bacteria. The bacterial purity or activity were ensured via staining methods and growth curves, respectively. Growth assays showed that the classic plate-counting method underestimated bacterial numbers compared with the bacterial counting method recommended by the reference material of the National Institutes for Food and Drug Control, China. The detection results of the UPT-LF assay differed significantly between the bacterial cultures in liquid and solid media and between different strains. Accelerated stability assessments and freeze-thaw experiments showed that the stability of the corresponding antigens played an important role in calibrating the UPT-LF assay. In this study, a new calibration system was developed for quantitative immunochromatography for detecting pathogenic bacteria. The results demonstrated the necessity of calibration for standardizing point-of-care testing methods.